The Europeanisation of international family law - Baarsma, N. A. (T. M. C. Asser Press, 2011)
In this book, the nature and reasons of the changes brought about by the transition from a national to a supranational choice of law approach are discussed in one particular field of international family law: the termination by dissolution of marriages and marriage-like registered partnerships. The current Dutch and the proposed European choice of law rules on divorce are examined and compared. Some Member States have strongly opposed the European proposal and no consensus could be reached.